Understanding the impact of climate change on oil palm plantation: a systematic literature review - Wulandari, Rina; Abas, Azlan; Abdullah, Abdullah (Frontiers in Sustainable Food Systems, 2025)
The impact of climate change on oil palm plantations has become a critical concern due to its effects on productivity and the physical conditions of oil palm trees. Unstable temperature and rainfall patterns contribute to plant stress, soil moisture fluctuations, and an increased frequency of extreme weather events, all of which affect oil palm growth and yield. This study aims to systematically review and analyze how climate change influences the productivity and physical conditions of oil palm. The present study integrates multiple research projects designs and follows the PRISMA statement (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) as the guideline for conducting systematic reviews. Web of Science (WoS) and Scopus were used as the primary databases to search for relevant articles. Through thematic analysis, this study categorizes the findings into four key themes: (a) economic and productivity aspects, (b) policies and adaptation strategies, (c) environmental and oil palm health, and (d) social and community wellbeing. The findings provide insights into how academics, practitioners, and policymakers can develop effective adaptation strategies to mitigate the impacts of climate change on oil palm plantations. This study recommends strengthening research on the physical effects of climate change on oil palm, developing climate-resilient oil palm varieties, and implementing advanced mitigation technologies to sustain oil palm productivity and industry resilience.